Reducing the Accumulative Charge on Fabric Filter Surfaces by Using a Bipolar Precharger - Pei Jia; Manqing Lin (Aerosol and Air Quality Research)
Abstract This study fabricated a wire-tube bipolar precharger with one power supply to reduce the amount of charge accumulated on fabric filters and improve collection efficiency in a hybrid electrostatic filtration system. Theoretical analyses revealed that electrons and negative and positive ions were produced under one negative power supply in the bipolar precharger simultaneously. Charged particles of opposite polarity, which escaped from the electric field with gas flow, deposited on the filter. Thus, the accumulative charge on fabric filter reduced due to charge neutralization. The influence of unipolar and bipolar prechargers on charge accumulation on the filter was experimental investigated. According to the maximum corona current, the optimized basic wire-tube electrode configuration was 120 mm in span of the tubes, 80 mm in wire-tube spacing, and 25 mm in tube diameter. The current on the filter, which was one order of magnitude lower than that in the precharger, was quadratic to the applied voltage on the precharger, and proportional to the gas velocity. Under gas velocities between 0.1 and 0.3 m s−1, despite the corona current of the bipolar precharger was approximately 5% higher than that of the unipolar precharger, the accumulative charge on fabric filter surfaces was approximately 40%–50% lower than that of the filtration system with a unipolar precharger. The incorporation of a bipolar precharger into hybrid electrostatic filtration systems is a promising approach for reducing the risk of back corona and spark damage to the filter bag.